(untitled) (Physical Education, Health and Social Sciences, 2026)
Introduction Intraoperative nausea and vomiting (IONV) are common during cesarean sections under spinal anesthesia, affecting up to 80% of patients. Despite advances in anesthesia, IONV continues to impact maternal comfort and satisfaction. Understanding its multifactorial causes is essential, particularly in underrepresented populations. Objective To determine the incidence and identify risk factors associated with intraoperative nausea and vomiting among parturient undergoing cesarean section under spinal anesthesia in a tertiary care hospital in Peshawar, Pakistan. Methodology A descriptive cross-sectional study was conducted at Hayatabad Medical Complex from March to July 2025. A total of 200 women undergoing cesarean section under spinal anesthesia were enrolled. Data on demographic, obstetric, anesthetic, and intraoperative characteristics were collected using a structured proforma. Associations between various risk factors and IONV were analyzed using Chi-square tests via SPSS version 27, with a p-value < 0.05 considered statistically significant. Result The incidence of intraoperative nausea was 18%, while vomiting occurred in 4.5% of participants. Nausea was more commonly reported after delivery (18%) than before (9%). Significant associations were found between IONV and higher BMI (>35 kg/m²) as well as a history of motion sickness (p < 0.001 for both). Vomiting was significantly more prevalent among primigravida women (p = 0.034). Intraoperative hypotension occurred in 13.5% of cases but did not show a statistically significant relationship with nausea. Conclusion Intraoperative nausea and vomiting remain prevalent during cesarean section under spinal anesthesia, particularly among women with elevated BMI and a history of motion sickness. Targeted preventive strategies for high-risk groups, including early antiemetic administration and individualized anesthetic management, may enhance maternal comfort and surgical outcomes. Further research is warranted to explore ethnic and regional variations in IONV to inform context-specific interventions Keywords Spinal Anesthesia, Cesarian Section, Incidence